Bibliometric analysis of scientific literature on the use of suppositories in the treatment of prostate cancer patients - I. V. Bushuieva; M. V. Parchenko; O. O. Maliuhina (Zaporozhye State Medical University, 2024)
Nowadays, cancer remains one of the main causes of death worldwide. Statistical data from various literary sources indicate that more than 130,000 people in Ukraine receive this diagnosis as a sentence every year. Cancer can affect any organs of the human body and, over time, the entire organism. In 2024, the agency of the World Health Organization on cancer and the International Agency of Cancer Research published the latest statistical estimates of this pathology in a global format, where prostate cancer is among the five most common oncological pathologies and takes the fourth place. Oncological diseases are one of the priority areas of healthcare development in accordance with the Order of the Ministry of Health of Ukraine No. 1832 dated 07.10.2022 "On Approval of Priority Areas of Healthcare Development for 2023-2025". It was this fact that determined the choice of the direction of this research in the matter of finding information on the provision of pharmaceutical care, namely the use of a drug - a rectal suppository for the treatment of prostate cancer. The aim of the work is to carry out a bibliometric analysis and further generalize the data of the scientific literature to study the prognostic value and features of the prescription of suppositories in the treatment of prostate cancer. Materials and methods. The data search was conducted in the PubMed electronic database using the following key terms: "prostate cancer and suppositories", "prostate cancer". To monitor and analyze international scientific research, with the help of visualization tools and modern SciVal citation metrics using the online platform, bibliometric analysis can be performed. Using the VOSviewer functional program, bibliometric networks were constructed and visualized. Results. A map of the relationships between the most used keywords on the topics of "prostate cancer" and "prostate cancer and suppositories", grouped into clusters for the period from 1986 to 2024, was built. The clustering of the most used keywords on the subject of "prostate cancer" for the specified period is summarized. According to the bibliographic analysis, interest in the above topic was highest in 2014 and 2021. Conclusions. According to the bibliographic analysis, the interest in the subject of the patients' treatment with prostate cancer disease continues to grow from 1998 up to the present. The analysis of publication activity using the visualization tool of bibliometric networks VOSviewer for the period from 2014 to 2024 for the key words "prostate cancer" has shown the presence of 14 clusters. The largest cluster is devoted to modern methods of prostate cancer treatment, studies of gene rearrangement, target therapy, carcinogenesis.